Impact of sudden stratospheric warmings on the stratosphere-to-troposphere transport of ozone - Lee, Jaewon; Butler, Amy H.; Albers, John R.; Wu, Yutian; Lee, Simon H. (Geophysical Research Letters, 2025)
Sudden stratospheric warmings (SSWs) can significantly impact tropospheric weather systems. Previous studies suggest that SSWs may also influence stratosphere-to-troposphere transport (STT), but their spatial and temporal distribution and mechanisms are not fully understood. The complex relationships between SSWs and the El Niño-Southern Oscillation (ENSO) have also made it difficult to isolate the effects of SSWs on STT. From an idealized ENSO simulation with the WACCM4 model using a stratospheric origin ozone tracer, we investigate the effect of SSWs on the STT of ozone under different ENSO phases. We find a significant increase in lower tropospheric ozone from the SSW onset up to 3 months later over the Arctic, North America, and Europe, regardless of the ENSO phase. This study highlights the significant influence of SSWs on STT on a subseasonal scale. Our results also emphasize the need to consider SSWs when addressing the ENSO impact on STT.